PARTISIPASI WANITA KAWIN DALAM MENINGKATKAN PENDAPATAN KELUARGA MISKIN DI LINGKUNGAN BUKIT SELAMAT KECAMATAN WOLIO KOTA BAU-BAU - Wali Aya Rumbia; Nur Asizah (JEP (Jurnal Ekonomi Pembangunan), 2017)
Women have rights and obligations as well as equal opportunities with men in development in all fields starting from the level of planning, implementation, formulation of policies to decision making. Women also play a physical, mental, mind and opinion role and are responsible for activities that aim to increase family income. The study aims to determine the causes of the low income of poor families in the Bukit Selamat neighborhood and find out the participation of women as a husband's companion in increasing the income of poor families. The results of the study showed that the participation of married women in adding to the income of poor families in the Bukit Selamat neighborhood of Wolio District, Bau-Bau City was quite participating. The average income earned by respondents is between Rp.500,000-750,000 per month. Based on this, it is suggested that the participation of married women should be increased to increase family income and the need for skills education for women.